Editorial [Hot Topic: The Estimation of Lipophilicity for QSAR Studies (Guest Editor: Miroslav Kuchar)] - Kuchar, Miroslav (Current Computer - Aided Drug Design, 2006)
Lipophilicity is the molecular property, which plays a prominent role in the mutual interactions of biologically active substances. Therefore, it is not surprising that lipophilicity has been in the focus of attention at the study of the influence of external compounds on living bodies. The first attempts - more than century ago - to find the relationships between biological activity and lipid solubility are connected with the works of Mayer and Overton. The great contribution to the parametrization of lipophilicity and its use in the analysis of structure-biological activity relationships belongs to Hansch, Fujita and Leo and later to Rekker and Nys. The importance of lipophilicity for the behavior of the substance in biological system is derived from its driving force in the transport of compound from the site of administration to the site of action (pharmacokinetics) and with the similar weight on the ligand-receptor interactions at the targeted site (pharmacodynamics). Nevertheless, some difference exists between both cases: in the ligand-receptor binding, lipophilicity is manifested itself first of all by the hydrophobic interactions among the nonpolar parts of both molecules. The 1-octanol-water partitioning system was chosen as an arbitrary standard for the expression of lipophilicity. The standard shake-flask technique for the determination of partition coefficients, which is sometimes labourious and for highly lipophilic compounds inaccurate, can be substituted by various chromatographic techniques. TLC, HPLC, capillary electromigration chromatography (CEC) or immobilized artificial membrane (IAM) chromatography, usually in the reversed-phase mode, are the typical examples. In these experimental conditions, the mandatory requirement is fulfiled and the adsorption mechanism of retention is predominantly suppressed. Using lipophilicity parameters, we have to keep in mind the golden rule of QSAR analyses, that the more homogenous series of compounds is studied, the simpler and relevant results are achieved. The review contributions submitted to this issue can be divided to three categories. M. Charton and V. Khadikar with coworkers drew the attention to the theoretical computation of log P values using empirical, nonexperimental quantities. M. Charton utilized the hydrogen bonding contributions to lipophilicity and V. Khadikar summarized the recent results concerning the relations between topology of molecules and their lipophilicity. The next two contributions, i.e. of A. Nasal and R. Kaliszan and F. Barbato are devoted to the recent progress in the chromatographic methods in the evaluation of lipophilicity. Both contributions are comprehensive and offer the comparative view on the experimental results and techniques presented - HPLC methods in the first one and IAM chromatography in the second one. The last but not least contribution from M. Cronin is dealt with the influence of lipophilicity on toxic properties of chemical substances. The use of QSAR methodology in this field is of a great importance for the chemical and pharmaceutical industries and environmental sciences in general.